Induction and activation of meiosis and subsequent parthenogenetic development of growing pig oocytes using calcium ionophore A23187 - Sedmíková, Markéta; Burdová, Jana; Petr, Jaroslav; Etrych, Milan; Rozinek, Jirí; Jílek, Frantisek (Theriogenology, 2003)
The pig ovary contains a large number of growing oocytes, which do not mature in vitro and cannot be readily used in various biotechnologies. This study was conducted to determine the possibility of inducing meiotic maturation in growing pig oocytes with an internal diameter of 110 microm, which had developed partial meiotic competence. Most of these oocytes spontaneously stopped maturation at the metaphase I stage (68%); a limited number proceeded to the metaphase II stage (26%). Treatment with calcium ionophore A23187 (50 microM for 5 or 10 min) after 24h in vitro culture overcame the block at the metaphase I stage, and treated growing pig oocytes matured to the metaphase II stage (66%). Oocytes in which maturation had been induced by calcium ionophore were again treated with calcium ionophore. Up to 58% of the treated oocytes were activated. Parthenogenetic development in oocytes treated with ionophore for meiosis induction and activation was very limited. The portion which reached morula stage did not exceed 8% and at most 3% developed to the blastocyst stage.
Keywords: Parthenogenesis; meióza; calcimycin; Cleavage Stage, Ovum; Time Factors; ionofory; Calcimycin; Swine; Oocytes; partenogeneze; ženské pohlaví; zvířata; oocyty; Meiosis; časové faktory; stadium rýhování vajíčka; Ionophores; prasata; Female; Animals